Jurisprudence of the State Administrative Court in the Development of State Administrative Law - Syawaludin; Arif Wibowo (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
The State Administrative Court is a judicial body that has absolute authority to examine and resolve disputes in the field of state administration. The development of the jurisprudence of the State Administrative Court (Peratun) is indispensable for the development of state administrative law. The issues studied are the role of jurisprudence in the field of state administrative law and the role of the State Administrative Court in providing access to justice. The method used in this study is library research, namely research whose object of study uses library data in the form of books as a data source. The Supreme Court has made efforts to strengthen jurisprudence so that it can support the development of administrative law. The judge's decision is needed as a source of law. This is because it stems from dynamic legal dispute resolution. Then, jurisprudence can bring social change to society. The judge's decision-making process is also faster than the law-making process. The absolute competence of the wider State Administrative Court can provide easy access to justice where the public can submit complaints about factual actions of the Government in the field of public law. Jurisprudence as a source of law is needed to develop state administrative law by taking into account the development of society, social conditions, legal and political conditions. Jurisprudence produces general principles of good governance so that they can be used to administer government wisely